Regional experience with Brachiaria: Tropical America-savannas - Pizarro, Esteban A.; Valle, Cacilda Borges do; Keller-Grein, Gerhard; Schultze-Kraft, Rainer; Zimer, A.H. (International Center for Tropical Agriculture, 1996)
Brachiaria species have become important components of sown pastures in the humid lowlands of tropical America. This ecosystem occupies about 50 of Brazil; 60 of the area encompassed by Bolivia, Peru, and Ecuador; 14 of Mexico; and significant areas in other countries of the region. The cultivars most Comment* evaluated across sites are R decumbens cv. Basilisk, R brizantha cv. Marandu, R humidicola cv. Humidícola, and R dictyoneura cv. Llanero. Cultivar Basilisk is the most widely used in the region, because it adapts to a wide range of soils and is easy to manage and to establish from seed. However, it is highly susceptible to spittlebugs and is associated with photosensitization in cattle. Cultivar Marandu is resistant to spittlebugs, but requires soils of medium to high fertility and does not tolerate waterlogged sites. cultivars Llanero and Humidicola are better adapted to poorly drained soils, but have only medium to low nutritional quality. Soil compaction, spittlebug infestation, and runoff of soil nutrients are factors associated with Brachiaria pasture degradation in the humid tropics; however, few studies report on pasture reclamation. During the last 15 years, part of the large germplasm collection maintained at CIAT has been evaluated in the American humid tropics. Promising new accessions of Brachiaria have been identified as potentially productive, but more research is needed on their seed production, pest and disease tolerance, compatibility with legumes, persistence, and animal productivity.